REFERENCE AND COUNTER-REFERENCE IN UNIFIED HEALTH SSYTEM: CHALLENGES FOR INTEGRALITY - Cardoso dos Santos, Rodrigo; Dayane Gois Bispo, Laura; Luemmy de Lima Ferreira, Laíse; Júlia Lorena Santos de Souza, Júlia; Santana de Jesus , Laís; da Silva Teixeira, Víctor; Schiassi Hernandes, Raphaela; Alves dos Santos Silva, Rodrigo (Journal of Health Care, 2021)
Introduction: Integrality in health as a guiding principle of the Unified Health System in Brazil is constituted as a polysemic technical-operational concept that is present from specific advice on the biopsychosocial dimensions of the user, referrals that address the demand in a resolutive way. The reference and counter-reference in this sense allows the edification and ordering of the flows and transits of users in the Health Care Networks (RAS). Objectives: To identify and discuss the main challenges faced by the referral and counter-referral system in SUS and as a source brought from phenomena for completeness. Materials and methods: In November and December 2019 the bibliographic survey took place using the bases: SciELO (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature in Health Sciences), Pubmed and Scopus. After applying the exclusion criteria pre-treated by the authors, 14 studies were obtained that comprised the final sample of the present study. There was a description by simple and qualitative statistics of the data, mentioned in four categories. Results and Conclusions: Among the 14 elected studies, it was noted that the realization of studies in this area is predominant in the Northeast (35.71%) of the country. The topicality of the theme drew attention, the majority was published in 2019 (35.71% ), 12 of them (85.71%) were published in national journals. The design of the studies was predominantly cross-sectional (71.4%), of qualitative analysis (42.8%). The challenges were classified as difficulties in the technical-operational, logistical, communication and human resources segments related to the management of the reference and counter-reference system. Thus, it was possible to identify the situational panorama of the experiences with the reference and counter-reference system in SUS. s.